Falling Embers - Cowles, Catherine (Toronto: The PageSmith LLC, 2021)
"Calder Cruz was everything Hadley Easton should've stayed far away from. Firefighter. Single dad. Her brother's best friend. But Hadley was never very good at playing by the rules. One night-one kiss-changes everything, their friendship going up in flames. It doesn't matter that she still sees him every day at the fire station and at weekly Easton family dinners. Calder's nothing but a stranger she no longer recognizes, each stilted conversation and stony stare killing a little more of her soul. Until one moment changes everything yet again. A single threat is all it takes to send Calder charging back into Hadley's life with a vengeance. And it's clear that's where he's determined to stay. As long-buried embers light anew, those threats turn deadly. And it's clear that whoever's behind the keyboard will do whatever it takes to extinguish their flame for good"-- Provided by the publisher.
Keywords: Man-woman relationships -- Fiction; Romance Fiction